Oscillococcinum® for upper respiratory tract infections and exacerbations in COPD: an observational, prospective study (OXITUNIS) - Hichem Aouina; Anis Bamri; Aurélien Vesin; Karine Danno; Eléonore Aubry; Cécile Faure; Naoual Boujedaini (BioExcel Publishing Ltd, 2021)
Background: Upper respiratory tract infections (URTIs) are a major cause of exacerbations in patients with chronic obstructive pulmonary disease (COPD). We assessed the effectiveness of Oscillococcinum® in the protection from URTIs in patients with COPD who had been vaccinated against influenza infection over the 2018-2019 winter season. Methods: Patients (n=106; mean ± standard deviation age: 66.0 ± 10.3 years; 89.6% men) were randomized into two groups: group V received influenza vaccination only and group OV received influenza vaccination plus Oscillococcinum® (one oral dose per week from inclusion in the study until the end of follow-up, with a maximum of 6 months follow-up over the winter season). The primary endpoint was the incidence rate of URTIs (number of URTIs/1000 patient-treatment exposure days) during follow-up compared between the two groups. Results: There was no significant difference in any of the demographic characteristics, baseline COPD, or clinical data between the two treatment groups (OV and V). The URTI incidence rate was significantly higher in group V than in group OV (2.9 versus 1.2 episodes/1000 treatment days, difference OV-V = −1.7; p=0.0312). There was a significant delay in occurrence of an URTI episode in the OV group versus the V group (mean ± standard error: 48.7 ± 3.0 versus 67.0 ± 2.8 days, respectively; p=0.0158). Limitations to this study include its small population size and the self-recording by patients of the number and duration of URTIs and exacerbations. Conclusion: Oscillococcinum may decrease the incidence rate and delay the appearance of URTIs in patients with COPD.